Comments on Wilson and Jensen. - Demski, Joel S. (The Accounting Review, 1983)
The article presents the author's opinions on organization theory and auditing. The articles: "Auditing: Perspectives From Multi-Person Decision Theory," by Robert Wilson, and "Organization Theory and Methodology," by Michael C. Jensen, were published in the April 1, 1983 issue of the periodical "Accounting Review." The two articles have much in common. Both emphasize the fact that research on intra- and inter-organization equilibrium behavior is mushrooming and now able to accommodate accounting questions in a way never before feasible, or perhaps even imaginable. Wilson suggests that cost allocation may reflect rational (equilibrium) obfuscation in a financial-reporting context. Wilson emphasizes the importance of "reputation" as an explanatory variable in many economic relationships. Reputation-building is the major factor contributing to economies of scale in auditing. According to Jensen, accounting methods are chosen according to organizations' policies. The use of mathematics as a factor of production in the research process comes into the fore with Jensen's vision of two agency models.